2015
DOI: 10.1016/j.otsr.2015.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic arthroscopy in the treatment of minimally displaced lateral humeral condyle fractures in children

Abstract: Level IV, therapeutic case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Arthroscopy has been recently used as a diagnostic tool in this regard. 14 In case the cartilage was disrupted, an arthrotomy was performed for reduction and fixation. lt seems that magnetic resonance imaging can accurately provide the same information noninvasively.…”
Section: Salter Harris Type Ill and IV Fracturesmentioning
confidence: 99%
“…Arthroscopy has been recently used as a diagnostic tool in this regard. 14 In case the cartilage was disrupted, an arthrotomy was performed for reduction and fixation. lt seems that magnetic resonance imaging can accurately provide the same information noninvasively.…”
Section: Salter Harris Type Ill and IV Fracturesmentioning
confidence: 99%
“…Standard radiography has limitations in showing the epiphyseal cartilage of the distal humerus in children. Magnetic resonance imaging (MRI) [6,7] or arthroscopy [8,9] can assess the integrity of the articular cartilage, but the former method requires sedation. It is difficult for children to cooperate during the examination, so arthroscopy requires general anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…For the fracture with small displacement, conservative or surgical treatment is chosen, mainly based on the stability of the fracture, the existence of articular cartilage hinges determines the stability of LCF. 9 Therefore, for micro-displaced fractures whose stability can not be completely judged by X-ray lms, it is suggested that the integrity of articular cartilage hinges can be judged by elbow arthrography, 10 or the articular surface can be detected by arthroscopy, so as to determine whether cartilage hinges are broken or not, so as to avoid missed diagnosis and mistreatment of micro-displaced LCF in children. 9 There are also multicenter studies in China that LCF with displacement ≤ 2mm is prone to re-displacement.…”
Section: Selection Of Surgical Indications and Surgical Methodsmentioning
confidence: 99%